Going to work without educational qualifications: school-to-work transitions of early school leavers in Belgium. (20th April 2020) - Van Praag, Lore; Clycq, Noel
ABSTRACT: Risks of exclusion can occur in multiple forms and start early in life. Early school leavers are especially at risk of social exclusion as this is strongly related to turbulent school-to-work-transitions. These young people often find themselves in low-qualified work or unemployment. In this article, we explore the labour market experiences of early school leavers in Flanders, Belgium. In total, 15 in-depth interviews were conducted with nine early school leavers and analysed following a grounded theory approach. Our results demonstrate the difficulties early school leavers encounter in their transitions from school to work and their precarious situation in the labour market. Of particular relevance are the insights gained in revealing the perspectives of young people on the importance of educational qualifications, work experience and participation in the labour market, as well as the strategies they develop to enter the labour market without educational qualifications.